The attitude presented in the press published by the Polish Socialist Party towards Gypsies in the interwar period – social and political issues - GONTAREK, Alicja (Historia i Świat, 2021)
The publication discusses the Polish Socialist Party's (PPS) attitude to Gypsies and the Gypsy question in the interwar period from 1918 to 1939. An extensive search of the PPS press, including around 1600 articles on the Gypsy population, has shown that this issue also interested the PPS. However, the socialists had a decidedly negative attitude to Gypsies. This was conditioned by the fact that the party found itself in opposition to the government camp, which supported the aspirations of Gypsy kings from the Kwiek clan, and it was with them that the PPS identified Gypsies. Secondly, the strong ideologization of the party's press, based among other things on the cult of work, led to a rejection of the lifestyle of the majority of Gypsies, who represented a nomadic and semi-nomadic culture of life.